2023
DOI: 10.1093/jxb/erad279
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of the mechanism of stomatal development diversification

Abstract: Stomata are the structures responsible for gas exchange in plants. The established framework for stomatal development is based on the model plant Arabidopsis, but diverse patterns of stomatal development have been observed in other plant lineages and species. The molecular mechanisms behind these diversified patterns are still poorly understood. We recently proposed a model for the molecular mechanisms of the diversification of stomatal development based on the genus Callitriche (Plantaginaceae), according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…It has been shown that the timing between SPCH and MUTE expression differs between the development of two types of stomata: anisocytic (A) and nonanisocytic (NA) 51 . During stomatal differentiation, SPCH initiates and MUTE terminates the asymmetrical divisions of the meristemoid 49 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the timing between SPCH and MUTE expression differs between the development of two types of stomata: anisocytic (A) and nonanisocytic (NA) 51 . During stomatal differentiation, SPCH initiates and MUTE terminates the asymmetrical divisions of the meristemoid 49 .…”
Section: Resultsmentioning
confidence: 99%
“…In seed plants, FAMA regulates the formation of myrosin cells, Brassicales-specific idioblasts (Li & Sack, 2014; Shirakawa et al, 2014), which provides another example of SMF co-option. We recently identified the interspecific differences in the spatiotemporal patterns of SPCH and MUTE expression underlying the diversification of stomatal development patterns in the genus Callitriche (Plantaginacea) (Doll et al, 2021a, 2021b, 2023). This shows that SMFs also play a pivotal role in evolution at the species level.…”
mentioning
confidence: 99%